1980
DOI: 10.1002/1097-0142(19800815)46:4<764::aid-cncr2820460421>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Transitional mucosa and survival in human colorectal cancer

Abstract: The mucosa in 100 segments of colon and rectum resected for cancer were examined using light microscopy and histochemical techniques. The extent of abnormal or transitional mucosa was defined for each case. Transitional mucosa was present in 93 of 95 adenocarcinomas and one malignant melanoma. The average total length of transitional change was 3.4 cm and the maximum length was 19.5 cm. An inverse correlation was observed between the survival and the length of transitional mucosa around locally invasive (Dukes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 35 publications
(10 reference statements)
4
21
0
Order By: Relevance
“…The anti-SIMA MAb 4D3 showed a tendency for stronger staining associated with a less malignant phenotype, namely carcinoma of stage A/B, smaller size, better differentiation. Both 4D3 and 10B3 positive tumours had a lower lymphocyte infiltrate, a feature previously reported for histologically-defined 'mucinous tumours' (Pihl, 1984) and interpreted as an indication that mucins may 'shield' cancers from the host immune response (Greaves et al, 1980). Over 90% of colorectal cancers contained mucin reactive with the two anti-LIMA MAb 2C3 and 9B5 in extracellular mucinous lakes or glandular lumen secretions as observed with the anti-SIMA MAb.…”
Section: Discussionsupporting
confidence: 61%
“…The anti-SIMA MAb 4D3 showed a tendency for stronger staining associated with a less malignant phenotype, namely carcinoma of stage A/B, smaller size, better differentiation. Both 4D3 and 10B3 positive tumours had a lower lymphocyte infiltrate, a feature previously reported for histologically-defined 'mucinous tumours' (Pihl, 1984) and interpreted as an indication that mucins may 'shield' cancers from the host immune response (Greaves et al, 1980). Over 90% of colorectal cancers contained mucin reactive with the two anti-LIMA MAb 2C3 and 9B5 in extracellular mucinous lakes or glandular lumen secretions as observed with the anti-SIMA MAb.…”
Section: Discussionsupporting
confidence: 61%
“…Some investigators (Katsuyama et al, 1985;Reid et al, 1985) found a consistent reduction in the proportion of o-acyl sialic acid in colonic mucosa close to tumours, while in other studies (Rogers et al, 1978;Greaves et al, 1980) this change could not be detected. Additional reports (Lev et al, 1985;Muto et al, 1985;Sugihara & Jass, 1986) have suggested that sialic acid substitutions are a relatively common finding in a variety of disease states and are non-specific.…”
Section: Discussionmentioning
confidence: 93%
“…They include a variability in staining technique used in different laboratories (Williams, 1985) and a masking of one dye by another (McFadden et al, 1985). Despite these problems, sweeping conclusions have been drawn about the significance of HID/AB alterations in colonic disease, with some investigators finding the changes specifically associated with malignancy (Filipe, 1969;Filipe et al, 1980;Saffos & Rhatigan, 1977;Greaves et al, 1980;Shamsuddin et aI., 1981) and others considering them non-specific and reactive (Isaacson & Attwood, 1979;Listinsky & Riddell, 1981;Ehsanullah et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations